2012
DOI: 10.1167/iovs.11-8010
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Lymphatic Vessels in the Cornea Is Dependent on the Presence of Macrophages

Abstract: C57BL/6 mouse corneas have more endogenous CD11b(+) cells and lymphatic vessels. The endogenous lymphatic vessels, along with pro-inflammatory MPS, account for the high risk of corneal graft rejection in C57BL/6 mice. CD11b(+) and F4/80(+) MPS appear to have an important role in of the formation of new lymphatic vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 35 publications
(42 reference statements)
2
42
0
Order By: Relevance
“…Interestingly, macrophages decreased in inflammatory corneas after CXL, which should contribute to the regression of pathologic BVs and LVs in corneas, as macrophages play a key role in the induction of angiogenesis44, 45 and lymphangiogenesis46, 47, 48, 49 under pathological conditions in the cornea and in the maintenance of LVs 50. Furthermore, we also observed significant reduction in CD45 + leukocytes in suture‐induced inflammation in corneas after CXL treatment using riboflavin and UVA.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, macrophages decreased in inflammatory corneas after CXL, which should contribute to the regression of pathologic BVs and LVs in corneas, as macrophages play a key role in the induction of angiogenesis44, 45 and lymphangiogenesis46, 47, 48, 49 under pathological conditions in the cornea and in the maintenance of LVs 50. Furthermore, we also observed significant reduction in CD45 + leukocytes in suture‐induced inflammation in corneas after CXL treatment using riboflavin and UVA.…”
Section: Discussionmentioning
confidence: 52%
“…For instance, CD11b+macrophages are required for corneal lymphangiogenesis under pathological conditions (Maruyama et al, 2005, 2012). Similarly, Th17 cells promote angiogenesis in autoimmune diseases and malignancies through IL-17 (Chauhan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy corneas (Day 0), blood and lymphatic vessels were restricted to the limbus but some lymphatics extended in the cornea as previously described. 31 Three days after cauterization, significant hemangiogenesis was observed that persisted until day 21. This was followed by a strong blood vessel regression observed after 40 days.…”
Section: Time Course Corneal Lymph/angiogenesismentioning
confidence: 99%